Perceptions and use of e-mail among Universiti Utara Malaysia Staff: A Pilot Study - Packeer Mohamed, Shafinah Farvin; Ku-Mahamud, Ku Ruhana; Ramli, Razamin; Abdullah, Kamarudin (2017)
The use of e-mail has become common either for work purposes or personal usage. Despite its usefulness, complain about the overwhelming messages received which cause the users to have problem in managing those messages. Similar situation occurred among Universiti Utara Malaysia (UUM) staff. Thus, a pilot study was conducted to investigate its staff’s perception and use of e-mail in order to improve the e-mail service provided to them. This paper discusses the findings from the pilot study, which involves 41 UUM staff. Self-administered questionnaires were used to gather the data, while descriptive statistical analysis was used for data analysis. The findings of the study reveal that UUM staff appreciate the e-mail service. However they faced problems like limited storage size and overwhelming emails. They think that UUM e-mail is being abused by the repeating advertisements and news sent to them. The output of this study can be used as a guideline by the UUM management in revising its e-mail policy to serve better quality of email service